Pengaruh Metode High Intensity Interval Training Menggunakan Elevation Training Mask Terhadap Peningkatan Anaerobik Laktasid Pemain Futsal Putra UPI - Fahmi Wijaya; Ucup Yusup; Dikdik Zafar Sidik (Jurnal Kepelatihan Olahraga, 2022)
High intensity interval trainingis an effective and efficient method of endurance training consisting of several exercise cycles of short duration and each cycle using a combination of high-intensity exercise and interspersed rest with low-intensity exercise. The problem in this study is whether the application of the high intensity interval training method using an elevation training mask has an effect on increasing lactasid anaerobic ability. With the use of an elevation training mask that is used when undergoing the high intensity interval training method, it is expected to increase the lactasid anaerobic ability of UPI futsal players. The purpose of this study was to determine the effect of the high intensity interval training method using an elevation training mask on the increase in lactaside anaerobic ability of UPI male futsal players. The research method used in this research is the experimental method. The sample consisted of 10 people who were selected by purposive sampling based on the researcher's criteria. The research instrument used consisted of the Rast test and the Multitsgae Hurdle Jump test. The research design is a one group pretest-posttest design. To analyze the data used t-test. The results showed a significant increase in the method of high intensity interval training using an elevation training mask to increase the lactaside anaerobic ability of UPI male futsal players.